2021
DOI: 10.3390/pathogens10070853
|View full text |Cite
|
Sign up to set email alerts
|

The First Record of Echinococcus ortleppi (G5) Tapeworms in Grey Wolf (Canis lupus)

Abstract: The aim of this study is to confirm the presence and molecular identification of Echinococcus tapeworms in wolves from south-eastern Poland. An investigation was carried out on the intestines of 13 wolves from south-eastern Poland. The small intestines were divided into three equal segments. Each segment was separately examined using the sedimentation and counting technique (SCT). The detected Echinococcus tapeworms were isolated and identified by PCRs and sequencing (nad1 and cox1 genes). Additionally, DNA is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…Our study indicated that the other remaining genotypes were isolated from dogs in the UK (G4), Kenya and Brazil (G5). Curiously, in a recently published paper, G5 was isolated for the first time from grey wolves in Poland (Karamon et al ., 2021); however, this study was published after the time period of the systematic search for the current study, hence it could not be included. Today, G4 is known as an independent species, E. equinus , which appears to be exclusive for the family Equidae as intermediate hosts (donkeys, horses and zebras) without infectivity traits for humans (Smyth, 1977; Nakao et al ., 2013; Rojas et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study indicated that the other remaining genotypes were isolated from dogs in the UK (G4), Kenya and Brazil (G5). Curiously, in a recently published paper, G5 was isolated for the first time from grey wolves in Poland (Karamon et al ., 2021); however, this study was published after the time period of the systematic search for the current study, hence it could not be included. Today, G4 is known as an independent species, E. equinus , which appears to be exclusive for the family Equidae as intermediate hosts (donkeys, horses and zebras) without infectivity traits for humans (Smyth, 1977; Nakao et al ., 2013; Rojas et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, several influential factors have been determined regarding canine echinococcosis, including feeding on raw/contaminated offal, being a young dog and lack of deworming treatment by dog owners (Otero-Abad and Torgerson, 2013). There, also, exist sylvatic life cycles involving wild canids, mainly wolves ( Canis lupus ) and jackals ( Canis aureus ), and wild ungulates as intermediate hosts (Romig et al ., 2017; Karamon et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports on wolves showed that the prevalence rate of E. granulosus s.l. was 15% (18/120) in Italy [ 17 ], 15% (4/27) in Spain [ 18 ], 1.5% (1/68) in Portugal [ 19 ], 7.6% (1/13) in Poland [ 8 ], 3.8% (1/26) in Estonia [ 20 ], 4.2% (5/118) in Mongolia [ 9 ], 100% (1/1) in Iran [ 21 ], 27% (25/93) in Canada [ 10 ], and 62.6% (77/123) in the USA [ 22 ]. The prevalence of E. multilocularis was 0.3% (3/911) in France [ 23 ], 35.7% (40/112) in Slovakia [ 7 ], 5.9% (34/200) in Latvia [ 24 ], 3.4% (4/118) in Mongolia [ 9 ], 100% (1/1) in Iran [ 21 ], and 13% (12/93) in Canada [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of AE is restricted to the northern hemisphere, and Turkey, particularly the northeastern part, is highly endemic for AE in terms of human cases, ranking third in the world [ 5 , 6 ]. Echinococcosis has been reported in wolves worldwide; in Europe [ 7 , 8 ], Asia [ 9 ], and the America [ 10 ]. In Turkey, there is only one report of E. equinus and E. canadensis (G6/7) in gray wolves [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mt-NAD1 and CO1 gene regions of the collected worm's were amplified and then sequenced. Finally, E. ortleppi (G5) was first time reported in a wolf in Poland ( Karamon et al, 2021 ). In Mongolia, 118 wolves were examined and E. multilocularis was found in four wolves, whereas E. canadensis (G6/7) was defined in two and E. canadensis (G6/7) in three wolves ( Ito et al, 2013 ).…”
Section: Introductionmentioning
confidence: 96%